Distribution of the gap junction protein connexin 35 in the central nervous system of developing zebrafish larvae - Jabeen, Shaista; Thirumalai, Vatsala (Frontiers in Neural Circuits, 2013)
Gap junctions are membrane specializations that allow the passage of ions and small molecules from one cell to another. In vertebrates, connexins are the protein subunits that assemble to form gap junctional plaques. Connexin-35 (Cx35) is the fish ortholog of mammalian connexin-36, which is enriched in the retina and the brain and has been shown to form neuronal gap junctions. As a first step towards understanding the role of neuronal gap junctions in central nervous system (CNS) development, we describe here the distribution of Cx35 in the CNS during zebrafish development. Cx35 expression is first seen at 1 day post fertilization (dpf) along cell boundaries throughout the nervous system. At 2dpf, Cx35 immunoreactivity appears in commissures and fiber tracts throughout the CNS and along the edges of the tectal neuropil. In the rhombencephalon, the Mauthner neurons and fiber tracts show strong Cx35 immunoreactivity. As the larva develops, the commissures and fiber tracts continue to be immunoreactive for Cx35. In addition, the area of the tectal neuropil stained increases vastly and tectal commissures are visible. Furthermore, at 4-5dpf, Cx35 is seen in the habenulae, cerebellum and in radial glia lining the rhombencephalic ventricle. This pattern of Cx35 immunoreactivity is stable at least until 15dpf. To test whether the Cx35 immunoreactivity seen corresponds to functional gap junctional coupling, we documented the number of dye-coupled neurons in the hindbrain. We found several dye-coupled neurons within the reticulospinal network indicating functional gap junctional connectivity in the developing zebrafish brain.